ANALISIS PELAKSANAAN PROGRAM PROMOSI KESEHATAN DALAM PENCEGAHAN STUNTING DI PUSKESMAS - Bernadetha, Bernadetha; Hayati, Nur; Adnan, Yudi; Wirawan, Susilo; Millati, Rida' (Ensiklopedia of Journal, 2024)
Based on the results of the 2018 Basic Health Research, the national prevalence of stunting in 2018 was 30.8 percent. The prevalence consists of 11.5% very short and 19.3% short. Based on the results of the 2018 Riau Province Riskesdas by the Indonesian Ministry of Health, the incidence of stunting in Riau Province was 25.7%. Salo Regency is one of the highest ranked for stunting rates in Riau Province at (31.99%). The purpose of this study was to analyze how the health promotion program in the prevention of stunting at Puskesmas Salo Kiri Hilir. The study used an analytical qualitative method conducted at the Salo Kiri Hilir Health Center to 4 informants including promkes holders, nutrition holders. Mothers who have stunted children and the Head of the Puskesmas. The results showed that in general the implementation of the promkes program at the Salo Kiri Hilir Health Center has been running, but there are obstacles such as limited budget resources in supporting the implementation of the promkes program at the Salo Kiri Hilir Health Center. It is suggested that the Puskesmas Salo Kiri Hilir can be used as material for evaluating the Health promotion program at Puskesmas Salo Kiri Hilir in accordance with budget capacity.Keywords: Budget, Health Promotion, Health Center